Implementasi Standar ISO 15489 Dalam Perancangan SOP Kearsipan di Dinas Dukcapil Kabupaten Seluma - Nabila, Nisreina; Purwandari, Endina Putri; Ramadani, Niska (Rekursif: Jurnal Informatika, 2025)
The digital era encourages the transformation of archive management, demanding a standardized system. Based on Indonesian Law No. 43 of 2009, archives are classified into active and inactive. At the Dukcapil Office of Seluma Regency, the management of inactive archives is not yet supported by written guidelines, which poses a risk to information security and access. This research designs Standard Operating Procedures (SOP) based on ISO 15489 and integrates them with a digital archiving system. Qualitative methods were used to explore the process and its impact. The results show that the security score (62) and accessibility score (63) are still relatively low. The designed SOP serves as an operational reference and the foundation for the development of the digital archive information system, which has proven to enhance efficiency and compliance with regulations. This research makes an important contribution to archival policy and suggests evaluating the implementation of SOPs as well as developing a digital system prototype in future studies.